Method development and analysis of cypermethrin and λ-cyhalothrin in palm oil matrices and soil samples by gas chromatography / Badrul Hisyam Zainuddin - Badrul Hisyam, Zainuddin (2012)
determination of cypermethrin and λ-cyhalothrin residues in crude palm oil (CPO), crude palm kernel oil (CPKO), and soil samples using gas chromatography with electron capture detector (GC-ECD). The first half of the thesis studied the development and optimization of pesticides extraction from palm oil samples. Sample preparations were divided into two parts. The first part was the extraction step based on low-temperature extraction technique. Factors such as acetonitrile volume, decanting the liquid phase from the precipitated oil after low-temperature precipitation, and the freezing time were studied and optimized. In the second part, two different clean-up methodologies were tested for co-extractives elimination: (i) solid-phase extraction (SPE); and (ii) dispersive solid-phase extraction (d-SPE). In both techniques, different sorbents were studied and optimized. Finally, the optimized conditions were obtained using acetonitrile extraction followed by low-temperature precipitation. Then, oil extracts were cleaned-up using combined SPE employing graphitized carbon black (GCB) and primary secondary amine (PSA) as the optimized sorbents. The second half of the thesis studied the development and optimization of pesticides extraction from soil samples. Ultrasonic extraction (USE) was chosen as the extraction technique for both cypermethrin and λ-cyhalothrin. Extraction parameters such as extraction solvent (acetonitrile, ethyl acetate, and acetone), solvent volume (15, 20, and 25 mL), and duration of sonication (5, 10, 15, and 20 min) were comprehensively investigated and optimized. The optimized conditions were obtained using 15 mL of acetonitrile as the extraction solvent and 5 min as the duration of sonication.